'Imagined recovery' from the European crisis. (April 2015) - Belfrage, Claes
This introduction provides a brief overview of the bleak recovery prospects within the current project of European integration illuminated by the challenges facing the European Central Bank. It thus sets the scene for analyses of how and why the European Union reached this situation and the constraints on the construction of 'imagined recoveries' potentially able to bring about a better Europe and their translation into effective policies. It then outlines the critiques developed by the contributors to this special issue. These critiques, emerging from the Marxist tradition, express a pessimism of the intellect that leads to the recognition of the structural constraints on such progressive imagined recoveries. Nevertheless, they are also based on an optimism of the will, as they are intended to facilitate the construction of alternative imagined recoveries for and critical interventions in the project of European integration to create another, better Europe. As such, this introduction identifies how this collection of articles endeavours to contribute to exploit the desperate moment that the current project of integration finds itself in.